Real Justice, Real Impact with the Prosecutors in Action - Yofhan Wibianto, Muhamad; Hartiwiningsih, Hartiwiningsih; Gusti Ayu Ketut Rachmi Handayani, I (Lembaga Contrarius Indonesia, 2025)
The prosecution service, as dominus litis, plays a pivotal role in ensuring the balance between the principle of legality and the pursuit of substantive justice within the criminal justice system. The enactment of the 2023 National Criminal Code, which formally recognizes the concept of living law, represents a significant paradigm shift by requiring criminal law enforcement to respond to social values and local community norms rather than relying solely on a rigid textual framework. This study addresses two central research questions: first, how the Criminal Procedure Code structurally constrains prosecutorial authority at the investigation and pre-prosecution stages; and second, how the formal recognition of living law generates implementation challenges, including normative conflict, discriminatory application, and legal uncertainty. Using a normative juridical research method with statutory, conceptual, and comparative approaches, this study finds a fundamental paradox within the prosecutorial function. Although prosecutors possess formal legitimacy as controllers of criminal cases, they lack adequate legal instruments to exercise this authority substantively. The absence of clear operational standards for applying living law risks undermining legal certainty and weakening the principle of equality before the law. Comparative analysis of prosecutorial practices in Canada, the Netherlands, and Germany demonstrates alternative models that integrate restorative justice, legal pluralism, and prosecutorial supervision more effectively. This study concludes that strengthening the prosecutorial role requires not merely procedural reform of the Criminal Procedure Code, but also ethical reinforcement, professional capacity building, and judicial verification mechanisms to ensure alignment with constitution, and universal human rights principles.